Impact of Social Media: A Cross-sectional Survey - Nismen Lathif; Esha Lathif (BJPsych Open)
Aims: Social media has revolutionised our lives over the past two to three decades. With the advent of smartphones we see ourselves, family members, colleagues and general public whiling time away on social media platforms. In this context it would be prudent to explore the impact of social media and one’s thoughts on the future.